2015
DOI: 10.1021/acscentsci.5b00306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origins of Mesoscale Ordering in a Metalloamphiphile Phase

Abstract: Controlling the assembly of soft and deformable molecular aggregates into mesoscale structures is essential for understanding and developing a broad range of processes including rare earth extraction and cleaning of water, as well as for developing materials with unique properties. By combined synchrotron small- and wide-angle X-ray scattering with large-scale atomistic molecular dynamics simulations we analyze here a metalloamphiphile–oil solution that organizes on multiple length scales. The molecules associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 41 publications
6
59
0
Order By: Relevance
“…The amount of nitrate counterions (− e ) directly bound to each Ln III (+3 e ) is calculated to be around 2.9±0.5 for Ce 3+ and 2.9±0.6 for Yb 3+ , indicating that Ln III ions are nearly (∼97 %) charge neutralized by nitrates in organic phases. This decreases the electrostatic repulsion and allows the metalloamphiphile complexes to aggregate; a phenomenon that we recently investigated using small angle X‐ray scattering measurements . Very recently it was experimentally demonstrated that aggregates in metalloamphiphile‐in‐organic solutions are not strictly charge neutral …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The amount of nitrate counterions (− e ) directly bound to each Ln III (+3 e ) is calculated to be around 2.9±0.5 for Ce 3+ and 2.9±0.6 for Yb 3+ , indicating that Ln III ions are nearly (∼97 %) charge neutralized by nitrates in organic phases. This decreases the electrostatic repulsion and allows the metalloamphiphile complexes to aggregate; a phenomenon that we recently investigated using small angle X‐ray scattering measurements . Very recently it was experimentally demonstrated that aggregates in metalloamphiphile‐in‐organic solutions are not strictly charge neutral …”
Section: Resultsmentioning
confidence: 98%
“…The four solutions were studied using all‐atom, explicit‐solvent MD simulations with a polarizable force field. To guarantee that our systems were well equilibrated, annealing simulations were performed followed by production simulations, which were run longer than the previous atomistic simulations using polarizable force field ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations